Tecarterapia na adiposidade abdominal - Ida, Adriana Mitie (2023)
Central obesity is one of the main causes of cardiovascular diseases in Brazil and worldwide. And middle-aged women change their body composition when they enter the perimenopause (pre-menopause) period, due to hormonal changes, a sedentary lifestyle and an unbalanced diet. As a result, they accumulate adiposity located in the abdominal region, increasing the incidence of chronic diseases. There are surgical resources that can reduce localized adiposity. However, the cost is high, requires recovery time and has risks inherent to the surgical technique used. Due to this, the search for therapeutic resources that aim to reduce abdominal adiposity in a noninvasive way has increased. Among the various existing resources, Tecartherapy is one of the non-invasive modalities that has been growing, as studies in the area have increased in recent years. Given the few, but recent, evidence found, enabling innovative action, this research aimed to develop a treatment protocol based on Tecartherapy to reduce localized abdominal adiposity in middle-aged women. The study included 23 healthy women aged between 40 and 55 years, with a BMI below 30 kg/h² and who had not entered menopause. Two assessments were carried out, one at the beginning of treatment and another at the end. During the evaluation, anthropometric data were collected and perimetry was performed at four points in the abdominal region, measuring the thickness of the adipose tissue using ultrasound and plycometry. And in two participants, an evaluation was carried out using a Magnetic Resonance Imaging exam to measure the thickness of the adipose tissue in the abdomen. The volunteers received six applications of Tecartherapy once a week with a combination of capacitive and resistive tips for 40 minutes. The results showed a reduction in abdominal circumference (p<0.05) and the thickness of the subcutaneous adipose layer (p<0.05). The result was enhanced in those who practiced physical activity three or more times a week. It can be concluded that Tecartherapy used with the combination of capacitive and resistive tips is effective for the treatment of localized abdominal fat reduction.